O ENSINO DE ESTATÍSTICA: UMA CONTRIBUIÇÃO PARA OS PROFESSORES DOS ANOS INICIAIS DA EDUCAÇÃO BÁSICA - Dalcin, Dulcinéia (2023)
The research carried out is part of the research line "Teacher Training" of the Professional Master's Degree in Teaching Science and Mathematics at the Franciscan University. The main objective was to develop a training workshop in statistics aimed at teachers in the early years of elementary school, aiming to improve the teaching of this thematic unit. To achieve this objective, a qualitative approach was adopted, which involved a bibliographical and documentary search to theoretically support the construction of the workshop. In addition, a quantitative approach was used, through reflection and analysis of a questionnaire applied to 35 teachers from the municipal network of Júlio de Castilhos, who work in the early years of Elementary School. Based on the data collected, it was possible to develop a workshop for teachers in the early years of the Municipal Education Network, which presented specific activities to work on teaching statistics at this level of education. During the workshop, which was systematized as an Educational Product, the teachers had the opportunity to realize the importance of leaving the theoretical context and bringing statistics to the practical environment, using simple materials, such as paper and pencil, so that students could record data, build graphs and tables, and reflect on statistical concepts in a concrete way. This shared learning experience in the workshop allowed participants to feel more confident about introducing statistical literacy into their classrooms, helping students to develop statistical skills from an early age and preparing them to deal with information and data in a critical and conscious way.